Potensi Campuran Ekstrak Air Daun Salam (Syzygium polyanthum) dan Daun Sambiloto (Andrographis paniculata) sebagai Terapi Adjuvan dalam Tatalaksana Penyakit Diabetes Melitus Tipe 2 di Indonesia - Meidina, Adinda Nezma; Ramadhanti, Nafilah; Triandra, Akbar; Putri, Yolanda Delia; Muftaridi, Rajwa Fairuz Putri (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disorder that continues to increase in prevalence every year, especially in Indonesia. In molecular mechanisms, T2DM is closely related to oxidative stress and inflammation. This literature review is intended to further examine the potential of a mixture of aqueous extracts of S. polyanthum and A. paniculata leaves as an adjuvant therapy for T2DM in Indonesia. Methods: Literature was searched using Google Scholar, Scopus, ResearchGate, and NCBI search sites. Inclusion and exclusion criteria were used to eliminate unrelated literature, resulting in 23 pieces of literature. Discussion: Based on phytochemical screening, S. polyanthum leaves and A. paniculata leaves contain compounds with beneficial effects in modulating the metabolic profile of T2DM patients by reducing oxidative stress, inhibiting ?-glycosidase, increasing insulin levels, regenerating pancreatic ?-cells, increasing glycolytic enzyme activity, and reducing pro-inflammatory biomarker levels. Conclusion: The mixture of aqueous extracts of S. polyanthum and A. paniculata leaves or combined with conventional drugs in the treatment of T2DM showed significant antidiabetic effects.